Identification of a nonstructural DNA-binding protein (DBP) as an antigen with diagnostic potential for human adenovirus. - Li Guo (PLoS ONE, 2013)
BACKGROUND: Human adenoviruses (HAdVs) have been implicated as important agents in a wide range of human illnesses. To date, 58 distinct HAdV serotypes have been identified and can be grouped into six species. For the immunological diagnosis of adenoviruses, the hexon protein, a structural protein, has been used. The potential of other HAdV proteins has not been fully addressed. METHODOLOGY/PRINCIPAL FINDINGS: In this study, a nonstructural antigenic protein, the DNA binding protein (DBP) of human adenovirus 5 and 35 (Ad5, Ad35) - was identified using immunoproteomic technology. The expression of Ad5 and Ad35 DBP in insect cells could be detected by rhesus monkey serum antibodies and healthy adult human serum positive for Ad5 and Ad35. Recombinant DBPs elicited high titer antibodies in mice. Their conserved domain displayed immunological cross-reactions with heterologous DBP antibodies in Western blot assays. DBP-IgM ELISA showed higher sensitivity adenovirus IgM detection than the commercial Adenovirus IgM Human ELISA Kit. A Western blot method developed based on Ad5 DBP was highly consistent with (χ(2) = 44.9, P<0.01) the Western blot assay for the hexon protein in the detection of IgG, but proved even more sensitive. CONCLUSIONS/SIGNIFICANCE: The HAdV nonstructural protein DBP is an antigenic protein that could serve as an alternative common antigen for adenovirus diagnosis.